Utilization Of Bookkeeping Applications as Manual Bookkeeping Solutions On CV. AJM - Septian, Bagas Arya; Sungkono, Sungkono (Integrasi Sains Media, 2023)
Bookkeeping is something that business actors must apply. Bookkeeping can be done both manually and computerized. In the development of an increasingly advanced era, the role of technology certainly has a major influence in the business world, especially in processing company financial data. In recording transactions, a computerized system is needed to make it easier for companies to record and the need to present a fast and accurate financial statement. This study aims to analyze what problems are often faced by CV AJM while implementing a manual bookkeeping system and providing solutions to these problems. The research method used is descriptive qualitative based on primary data sources and secondary data obtained by conducting field research. The result of this study is to explain good financial document filing, recording of financial statements, and guidelines for using accounting bookkeeping applications that can help CV AJM manage business activities. So that with this computerized bookkeeping can help workers quickly and accurately; later, business owners can use these financial statements as study material to analyze their business and be able to maintain their business in the future.